BANTUAN HUKUM BAGI ANGGOTA KEPOLISIAN YANG MELAKUKAN TINDAK PIDANA PADA SIDANG KOMISI KODE ETIK - Irwan Sukma; Otong Rosadi (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
A member of the National Police who allegedly violates the code of ethics of the Police profession is given the right to defend himself and get help and accompanied by a companion appointed by the Supreme Court (Ankum) originating from the Internal Police as stipulated in Chief of Police Regulation Number. 7/2005 on Procedures for Granting Legal Assistance and Advice in the Police Force of the Republic of Indonesia . In the KKEP Assembly legal aid to the alleged infringer was given, but empirically impressed only the formalities to meet the existing provisions, so as not to realize the objectives and the nature of providing legalassistance for alleged offenders as in the case of the Commission Police Codes Committee (KKEP) which occurred by the Padang City Police Department.